Mitochondria in hypoxic pulmonary hypertension, roles and the potential targets - Geng, Yumei; Hu, Yu; Zhang, Fang; Tuo, Yajun; Ge, Rili; Bai, Zhenzhong (Frontiers in Physiology, 2023)
Mitochondria are the centrol hub for cellular energy metabolisms. They regulate fuel metabolism by oxygen levels, participate in physiological signaling pathways, and act as oxygen sensors. Once oxygen deprived , the fuel utilizations can be switched from mitochondrial oxidative phosphorylation to glycolysis for ATP production. Notably, mitochondria can also adapt to hypoxia by making various functional and phenotypes changes to meet the demanding of oxygen levels. Hypoxic pulmonary hypertension is a life-threatening disease, but its exact pathgenesis mechanism is still unclear and there is no effective treatment available until now. Ample of evidence indicated that mitochondria play key factor in the development of hypoxic pulmonary hypertension. By hypoxia-inducible factors, mutiple cells sense and transmit hypoxia signals, which then control the expression of various metabolic genes. This activation of hypoxia-inducible factors considered associations with crosstalk between hypoxia and altered mitochondrial metabolism, which plays an important role in the development of hypoxic pulmonary hypertension. Here, we review the molecular mechanisms of how hypoxia affects mitochondrial function, including mitochondrial biosynthesis, reactive oxygen homeostasis, and mitochondrial dynamics, to explore the potential of improving mitochondrial function as a strategy for treating hypoxic pulmonary hypertension.